Profil Keterampilan Berpikir Kritis Siswa SMA pada Materi Usaha dan Energi: Analisis Berdasarkan Indikator Facione - El Syahrie Maghfira; Hera Novia; Amsor (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to describe the profile of high school students’ critical thinking skills on the topic of work and energy based on Peter A. Facione’s critical thinking indicators. The research employed a quantitative approach with a descriptive method. The sample consisted of 52 tenth-grade students of SMA Al-Ma’soem in the 2024/2025 academic year, selected using purposive sampling techniques. The research instrument was an essay test developed based on six Facione indicators, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation. Data were analyzed using quantitative descriptive techniques through percentage calculations for each indicator achievement. The results showed that students’ critical thinking skills were categorized as high. The evaluation indicator obtained the highest percentage at 70.41%, while the explanation indicator achieved the lowest percentage at 66.12%. The low achievement in the explanation indicator indicates that students still experience difficulties in constructing scientific arguments systematically. This study demonstrates that physics learning on the topic of work and energy is capable of developing students’ critical thinking skills, although explanation skills still need improvement.